Foye's principles of medicinal chemistry - Roche, Victoria F.; Zito, S. William; Lemke, Thomas L.; Williams, David A. (Philadelphia : Wolters Kluwer, 2020)
"With expert contributions from experienced educators, research scientists and clinicians, Foye's Principles of Medicinal Chemistry, Eighth Edition is an invaluable resource for professional students, graduate students and pharmacy faculty alike . This 'gold standard' text explains the chemical basis of drug action, emphasizing the structure-activity relationships, physicochemical-pharmacokinetic properties, and metabolic profiles of the most commonly used drugs"--
Includes bibliographical references and index.
Keywords: Pharmaceutical Chemistry